The sequestration and storage model of atmospheric carbon dioxide - Ferrufino, G. L.A.A. [UNESP]; Carvalho, J. A. [UNESP]; Nascimento, L. F.C. (My University, 2009)
Carbon dioxide (CO2) is the most important greenhouse gas. A gradual increase on its atmospheric concentration threatens significantly the climate. One of the main challenges of environment planning is to identify a model that connects all factors that determine the carbon cycle, that is, ocean-terrestrial ecosystem-anthropogenic emissions-atmosphere. Basic thermodynamic principles can be applied in a statistical modeling with historic time series to obtain atmospheric CO2 concentration, creating the possibility of construction of scenarios that will help decision making. A model that links all carbon cycle factors was developed in this dissertation work, focusing in four thermal of climatic zones (Boreal, Temperate, Tropical, and Polar) for calculations of atmospheric CO2 storage. It was developed with nonparametric models based in carbon dioxide records from station measurement: EIA (Energy Information Administration), CDIAC (Carbon Dioxide Information Analysis Center), FAO (Food and Agriculture /organization), SIO (Scripp Institution Oceanography), etc. Results show that in 2100, the atmospheric CO2 concentration will reach a value four times higher than that of the preindustrial period. The temperate zone already emits almost half of the carbon dioxide to the atmosphere; by 2100, this emission will increase 15 times more than that corresponding to the tropical zone. China will be responsible for emissions in a proportion of 24 to 11 in comparison to that of the United States. Stabilization of CO2 concentrations in the atmosphere will be obtained when the anthropogenic carbon dioxide emissions attain a decrease of at least 34% in 2100 in the temperate zone
Keywords: Carbon capture; Chemisorptions system CO2; Optimization process